Expression of p53, p21 and p16 does not correlate with response to preoperative chemoradiation in gastric carcinoma - Sirák, Igor; Petera, Jiří; Hatlová, Jana; Vošmik, Milan; Melichar, Bohuslav; Dvořák, Josef; Tyčová, Věra; Zoul, Zdeněk; Leško, Michal (Hepato-gastroenterology, 2009)
BACKGROUND/AIMS: A retrospective evaluation was oerformed to determine whether the intensity of p53, p21 or p16 expression predicts response to preoperative chemoradiotherapy in locally advanced gastric carcinoma. METHODOLOGY: Thirty-six patients (cT2-4 or N+) were studied. Preoperative treatment consisted of 30-45Gy of radiation with continuous 5-fluorouracil and weekly cisplatin. Expression of p53, p21 and p16 in pretreatment biopsies was assessed by immunohistochemistry. Level of expression was determined from the intensity and extent of staining. Tumor downstaging was defined as a reduction of at least one T-stage level and/or finding of intense tumor regression in histopathologic examination. RESULTS: Seventeen patients responded to chemoradiation: 8 patients had pathologic complete response, 9 patients were downstaged. The multivariate analysis showed no significant influence of p53 (p = 0.76), p21 (p = 0.10) nor p16 (p = 0.70) expression upon tumor response. Response was found in 52% of patients with low, and in 40% of patients with high p53 staining (p = 0.21); in 54% of patients with low, and in 30% of patients with high p21 staining (p = 0.14); and in 48% of patients with low, and in 43% of patients with high p16 staining (p = 0.32). CONCLUSIONS: We found no significant influence of p53, p21 nor p16 expression upon response to preoperative chemoradiotherapy in gastric carcinoma.
Keywords: Carcinoma; nádory žaludku; Chi-Square Distribution; kombinovaná terapie; nádorové proteiny; Humans; lidé středního věku; Female; Aged; Radiotherapy Dosage; dospělí; protokoly protinádorové kombinované chemoterapie; financování organizované; celková dávka radioterapie; Financing, Organized; senioři; lidé; Immunohistochemistry; Tumor Markers, Biological; imunohistochemie; rozdělení chí kvadrát; karcinom; Cyclin-Dependent Kinase Inhibitor p21; Adult; staging nádorů; ženské pohlaví; Male; Middle Aged; Retrospective Studies; Antineoplastic Combined Chemotherapy Protocols; Aged, 80 and over; předoperační péče; senioři nad 80 let; retrospektivní studie; Neoplasm Staging; Combined Modality Therapy; Neoplasm Proteins; mužské pohlaví; Preoperative Care; Stomach Neoplasms; inhibitor p21 cyklin-dependentní kinasy; Tumor Suppressor Protein p53